A Simulation Study of ZnO/Si Based Efficient UV-Photodetector in COMSOL Multiphysics - Yadav S.M.; Pandey A. (My University, 2025)
This paper reports a simulation study of ZnO/Si-based photodetection structure in COMSOL Multiphysics. The optical performance of the resultant device has been explored under a broad light illumination with a uniform optical power of 10 μW. The photon conversion parameter of the resultant device, known as responsivity, has been measured for a broad (UV-visible) spectrum. The obtained results show the potentiality of the ZnO/Si structure for UV illumination detection. The proposed device shows the responsivity of 4.5 A/W for 380 nm illumination at -2 V. The efficient light detection along with the low detection volume of the device has proven its potential impact on optoelectronics applications including UV detection © 2023 IEEE.